Seller-Required Mortgage Preapprovals and the Homebuying Process. Issue 4 (14th December 2021) - Winkler, Daniel T.; Lipscomb, Clifford A.; Gordon, Bruce L.
Abstract: Mortgage preapprovals have been commonly available for about 20 years. A buyer may benefit from a mortgage preapproval by increasing the likelihood of closing on the loan. A seller with an offer from a preapproved buyer is exposed to less risk of a transaction not closing and perhaps a quicker average time to closing. The findings show that commercial sellers are more likely to require preapprovals, especially for REO transactions. Time until the closing of a sale (TUS) is about 4.2% quicker for transactions with seller-required preapprovals. Time until the signing of a sales contract (TUC) is not less for seller-required preapprovals, but it is 15.3% quicker for REO preapproval sales. The selling price discount for preapproval properties averages 1.7%–3% for non-REOs and 3%–4% for REO properties.